2007
DOI: 10.1111/j.1348-0421.2007.tb03928.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Polymorphonuclear Leukocytes Treated with the Culture Filtrate of Aspergillus fumigatus and Gliotoxin

Abstract: Pathogens of the Aspergillus species are frequently seen in deep‐seated mycoses. We previously demonstrated that the culture filtrate of Aspergillus fumigatus (CF) has immunosuppressive effects on polymorphonuclear leukocytes (PMNs), which act as the main phagocytes to hyphae of Aspergillus fumigatus (A. fumigatus). But little is known about the gene expression profiles involved in it. Therefore we investigated the changes in gene expression in human PMNs treated with CF or gliotoxin at two time points, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Studies have found that remnant A. fumigatus can be transformed from conidia to mycelium form within PMNs, suggesting an important role for PMNs in mycelium removal. This model has been supported by other studies wherein cultured diffusates of A. fumigatus (AfDs) were shown to have immunosuppressive effects on PMNs (Higurashi et al, 2007). Previous studies have elucidated an indispensable role for PMNs in the clearance of A. fumigatus (Ikegami et al, 1998).…”
Section: Introductionsupporting
confidence: 68%
“…Studies have found that remnant A. fumigatus can be transformed from conidia to mycelium form within PMNs, suggesting an important role for PMNs in mycelium removal. This model has been supported by other studies wherein cultured diffusates of A. fumigatus (AfDs) were shown to have immunosuppressive effects on PMNs (Higurashi et al, 2007). Previous studies have elucidated an indispensable role for PMNs in the clearance of A. fumigatus (Ikegami et al, 1998).…”
Section: Introductionsupporting
confidence: 68%
“…Most studies on the mechanisms of GT action have focused on its proapoptotic effects in mammalian cells (7). Nonetheless, a recent gene expression profiling study of human polymorphonuclear neutrophils exposed to GT demonstrated broad-spectrum changes on the host transcriptosome (8). In addition to its direct immunosuppressive properties, GT also affects other important cellular functions, such as actin cytoskeleton organization (3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CDC42 induces phagocytosis in macrophages via FcγR [ 34 ]. A study using human polymorphonuclear leukocyte (PMNs) showed that BCAR3 was down-regulated by gliotoxin, a mycotoxin produced by A. fumigatus , which further enhances the importance of this gene in the host immune response during fungal infection [ 35 ]. Early Growth Response 2 (EGR2) is a transcription factor closely related to HOXA4 gene and has been shown to be up-regulated during C. albicans infection in bone marrow derived macrophages [ 36 ].…”
Section: Resultsmentioning
confidence: 99%